Management strategy for facial venous malformations - Kumar, Shailendra (Medknow Publications & Media Pvt Ltd, 2014)
Venous malformations (VMs) are slow-flow vascular malformations, caused by abnormalities in the development of the veins. Venous malformations vary in size and location within the body. When the skin or tissues just under the skin are affected, they appear as slightly blue-colored skin stains or swellings. These can vary in size from time to time because of swelling within the malformation. As these are vascular malformations, they are present at birth and grow proportionately with the child. Venous malformations can be very small to large in size, and sometimes, can involve a significant area within the body, When the venous malformation is well localized, this may cause localized swelling, however, when the venous malformation is more extensive, there may be more widespread swelling of the affected body part. Some patients with venous malformations have abnormal blood clotting within the malformation. Most venous malformations cause no life-threatening problems for patients. Some venous malformations cause repeated pain due to intermittent swelling and congestion of the malformation or due to the formation of blood clots within the malformation. Rarely, venous malformations may be part of a syndrome (an association of several clinically recognizable features) or be linked to an underlying genetic abnormality. We present 12 cases of venous malformations of the head and neck area, which have been managed at our hospital.